Transcriptome analysis of mammary epithelial cell between Sewa sheep and East FriEsian sheep from different localities - Rui Li; Junru Pan; Cheng Pan; Jingjing Li; Zhenzhen Zhang; Khuram Shahzad; Yu Sun; Quzhu Yixi; Wangjie Zhaxi; Haofeng Qing; Tianzeng Song; Wangsheng Zhao (BMC Genomics)
Abstract Mammary epithelial cells, the only milk-producing cell type in the mammary gland, undergo dynamic proliferation and differentiation during pregnancy, culminating in lactation postpartum. The East FriEsian sheep ranks among the world’s most prolific dairy breeds, while the Sewa sheep, a unique dual-purpose breed autochthonous to the Qinghai-Tibet Plateau, exhibits significantly lower milk production. Employing tissue culture methods, we successfully established mammary epithelial cell lines from both breeds. Morphological assessment of mammary epithelial cells and immunofluorescence identification of Cytokeratin 7 and Cytokeratin 8 confirmed the epithelial identity of the isolated cells. Subsequent RNA-seq analysis of these in vitro epithelial cell lines revealed 1813 differentially expressed genes (DEGs). Among these, 1108 were significantly up-regulated and 705 were down-regulated in Sewa epithelial sheep cells compared to East FriEsian epithelial cells. KEGG enrichment analysis identified cellular processes, environmental information processing, human diseases, metabolism, and organismal systems as the primary functional categories associated with DEGs. Gene ontology (GO) terms annotation, categorized into molecular function, biological processes, and cellular component, yielded “binding and catalytic activity,” “molecular function regulator activity,” and “cellular process,” “biological regulation,” and “regulation of biological process” as the top three terms within each domain, respectively. Clusters of Orthologous Groups of proteins (KOG) classification further revealed that “signal transduction mechanisms” accounted for the largest proportion of DEGs among all KOG categories. Finally, based on these analyses, ATF3 and MPP7 were identified as promising candidate genes for regulating lactation.